Elevated Plasma IL-37, IL-18, and IL-18BP Concentrations in Patients with Acute Coronary Syndrome - Qingwei Ji; Qiutang Zeng; Ying Huang; Ying Shi; Yingzhong Lin; Zhengde Lu; Kai Meng; Bangwei Wu; Kunwu Yu; Meng Chai; Yuyang Liu; Yujie Zhou (Hindawi Limited, 2014)
Objective. More recently, evidence showed that the novel anti-inflammatory cytokine interleukin- (IL-) 37 was expressed in the foam-like cells of atherosclerotic coronary and carotid artery plaques, suggesting that IL-37 is involved in atherosclerosis-related diseases. However, the plasma levels of IL-37 in patients with acute coronary syndrome (ACS, including unstable angina pectoris and acute myocardial infarction) have yet to be investigated. Methods. Plasma IL-37, IL-18, and IL-18BP levels were measured in 50 patients with stable angina pectoris (SAP), 75 patients with unstable angina pectoris (UAP), 67 patients with acute myocardial infarction (AMI), and 65 control patients. Results. The plasma IL-37, IL-18, and IL-18BP levels were significantly increased in ACS patients compared to SAP and control patients. A correlation analysis showed that the plasma biomarker levels were positively correlated with each other and with the levels of C-reactive protein (CRP), N-terminal probrain natriuretic peptide (NT-proBNP), and left ventricular end-diastolic dimension (LVEDD) but negatively correlated with left ventricular ejection fraction (LVEF). Furthermore, the plasma IL-37, IL-18, and IL-18BP had no correlation with the severity of the coronary artery stenosis. Conclusions. The results indicate that the plasma IL-37 levels are associated with the onset of ACS.